Development and characterization of high-affinity aptamers for HIV protease detection - Ana Valadés-Alcaraz; Roberto Reinosa; Mario González-Hevilla; Carlos Medina-Sánchez; África Holguín (Heliyon)
Background: There are 39 million people infected by the human immunodeficiency virus (HIV) and 1.3 million new annually infections with more than 150 variants circulating. Early HIV detection is crucial for timely antiretroviral therapy and transmission prevention, but no technique can detect HIV before 10 days of infection. Aptamers, single-stranded oligonucleotides, can recognize specific proteins with high affinity and specificity. New molecular assays based on aptamers selected against highly-conserved peptides in HIV proteins could help to detect the virus earlier. Results: We have selected and characterized the first two aptamers against a highly-conserved and exposed peptide in the HIV protease (PR) after analyzing 236,240/6,436 HIV-1/HIV-2 PR sequences of nearly 150 HIV variants (types/groups/subtypes/circulating recombinants) by new bioinformatics tools. The selected aptamers were characterized by bioinformatics analysis, exploring their affinity, sensitivity, specificity, and best combination by Enzyme-Linked-Oligonucleotide-Assays (ELONA). Different strategies were explored to increase sensitivity for HIV PR detection, and the best one could detect viral PR (3.13 ng, 3.76·108 virions/well) and also HIV in infected samples with viraemia >8 log. Significance: Our anti-HIV PR aptamers are a promissing tool to be incorporated into new nanotechnologies for an ultrasensitive detection of HIV proteins in clinical samples for an early diagnosis of all virus variants.